2004
DOI: 10.1128/mcb.24.24.10611-10620.2004
|View full text |Cite
|
Sign up to set email alerts
|

p38α Mitogen-Activated Protein Kinase Plays a Critical Role in Cardiomyocyte Survival but Not in Cardiac Hypertrophic Growth in Response to Pressure Overload

Abstract: The molecular mechanism for the transition from cardiac hypertrophy, an adaptive response to biomechanical stress, to heart failure is poorly understood. The mitogen-activated protein kinase p38␣ is a key component of stress response pathways in various types of cells. In this study, we attempted to explore the in vivo physiological functions of p38␣ in hearts. First, we generated mice with floxed p38␣ alleles and crossbred them with mice expressing the Cre recombinase under the control of the ␣-myosin heavy-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
185
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 211 publications
(195 citation statements)
references
References 41 publications
7
185
0
3
Order By: Relevance
“…This is in agreement with Liao et al, who demonstrated that overexpression of MKK3b or MKK6b induces cardiac fibrosis (Liao et al, 2001) as well as with Streicher et al showing that MKK3b overexpressing transgenic mice exhibit increased cardiac interstitial fibrosis and contractile dysfunction (Streicher et al, 2010) and with Zhang et al reporting reported reduced cardiac fibrosis in dominant negative p38α -transgenic mice (Zhang et al, 2003). Instead, following myocardial infarction p38α+MKK3b overexpression resulted in reduced apoptosis and reduced fibrosis , and in pressure overload model cardiac-specific p38α knock-out mice exhibited dilated cardiomyopathy, increased fibrosis and increased apoptosis (Nishida et al, 2004). The differences between the experimental settings may explain these contradictory findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with Liao et al, who demonstrated that overexpression of MKK3b or MKK6b induces cardiac fibrosis (Liao et al, 2001) as well as with Streicher et al showing that MKK3b overexpressing transgenic mice exhibit increased cardiac interstitial fibrosis and contractile dysfunction (Streicher et al, 2010) and with Zhang et al reporting reported reduced cardiac fibrosis in dominant negative p38α -transgenic mice (Zhang et al, 2003). Instead, following myocardial infarction p38α+MKK3b overexpression resulted in reduced apoptosis and reduced fibrosis , and in pressure overload model cardiac-specific p38α knock-out mice exhibited dilated cardiomyopathy, increased fibrosis and increased apoptosis (Nishida et al, 2004). The differences between the experimental settings may explain these contradictory findings.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found that in vivo adenoviral overexpression of MKK3b together with p38α led to a marked functional improvement in infarcted rat heart; the size of an infarction area was significantly reduced, apoptosis decreased and angiogenesis increased . In addition, Nishida et al showed that cardiac-specific knockdown of p38α led to increased cardiomyocyte apoptosis and adverse myocardial remodelling following pressure overload (Nishida et al, 2004). However, several studies have demonstrated that during myocardial ischemia, p38 MAPK inhibition protects against lethal injury (Saurin et al,2000;Bassi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Animal Models and Cross-breeding-APP/PS1 double transgenic mice over-expressing human mutated APP (KM670/ 671NL) and PS1 (L166P) under Thy-1 promoters (27) were kindly provided by M. Jucker, Hertie Institute for Clinical Brain Research, Tübingen, Germany; p38 fl/fl mice with loxP siteflanked mapk14 gene were imported from BioResource Center, RIKEN Tsukuba Institute, Japan (28); and Nex-Cre mice expressing Cre recombinase from the endogenous locus of the nex gene that encodes a neuronal basic helix-loop-helix (bHLH) protein were kindly provided by K. Nave, Max-PlanckInstitute for Medicine, Göttingen, Germany (29). All three mouse strains were on a C57BL6 genetic background.…”
Section: Methodsmentioning
confidence: 99%
“…Mice-Both the p38␣ floxed allele and p38␣ K14 mice were previously described (14,15). Mice bearing Mkk3 and Mkk6 null alleles were also previously described (16,17).…”
Section: Methodsmentioning
confidence: 99%